2013
DOI: 10.1071/fp12180
|View full text |Cite
|
Sign up to set email alerts
|

A multisite managed environment facility for targeted trait and germplasm phenotyping

Abstract: Field evaluation of germplasm for performance under water and heat stress is challenging. Field environments are variable and unpredictable, and genotype × environment interactions are difficult to interpret if environments are not well characterised. Numerous traits, genes and quantitative trait loci have been proposed for improving performance but few have been used in variety development. This reflects the limited capacity of commercial breeding companies to screen for these traits and the absence of valida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
74
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(74 citation statements)
references
References 51 publications
0
74
0
Order By: Relevance
“…Certainly, the DNA code may carry information that influences alternate plant responses to each new environment, but the way information is integrated throughout the growing season is critically determinant for crop yield at the physiological level and across the community of plants (Rebetzke et al, 2013). In this sense, field physiological evaluations of the germplasm performance for abiotic stress, as well as water and heat constraints are challenging.…”
Section: Resultsmentioning
confidence: 99%
“…Certainly, the DNA code may carry information that influences alternate plant responses to each new environment, but the way information is integrated throughout the growing season is critically determinant for crop yield at the physiological level and across the community of plants (Rebetzke et al, 2013). In this sense, field physiological evaluations of the germplasm performance for abiotic stress, as well as water and heat constraints are challenging.…”
Section: Resultsmentioning
confidence: 99%
“…Field-based, managed-environment methods have been advocated and utilised to enable genetic gain for important environmental components of the TPE that contribute to repeatable GÂE interactions (Fischer et al 1989;Cooper et al 1995Cooper et al , 1997Cooper et al , 2014Campos et al 2004Campos et al , 2006Kirigwi et al 2004;Trethowan et al 2005;Bänziger et al 2006;Weber et al 2012;Rebetzke et al 2013). Two maize breeding examples and the managed-environment solutions that have been implemented for the US corn-belt TPE to deal with important environmental components and the associated GÂE interactions are considered below: brittle snap resistance, and drought resistance.…”
Section: Improved Phenotyping Methodology: Managed Environmentsmentioning
confidence: 99%
“…Canopy temperature (CT) is an example of a widely used, high-throughput germplasm screening tool. CT is linked to stomatal conductance, an indirect indicator of water uptake by roots, especially under drought and heat stress [75,76]. In one study, researchers found that 60% of variation in yield from recombinant inbred lines grown under drought conditions was explained by CT [77].…”
Section: Crop Physiology and Genetics Under Climate Changementioning
confidence: 99%